Pengetahuan dan Sikap Ibu Hamil Tentang Risiko Paparan Covid-19 Terhadap Persiapan Persalinan Pada Masa Pandemi Covid-19 - Wuri Widi Astuti; Siti Asiyah (STIKES dan AKZI Karya Husada Kediri, 2022)
During the Covid-19 pandemic, implementing health protocols according to government recommendations is one of the efforts to prevent the transmission of the virus that must be obeyed by all groups, including pregnant women. Pregnant women are a vulnerable group exposed to Covid-19 virus infection which can increase maternal and newborn morbidity and mortality. The purpose of the study was to analyze the relationship between knowledge and attitudes about the risk of exposure to Covid-19 with preparation for childbirth during the Covid-19 pandemic at the Wilangan Nganjuk Health Center. This type of research is a correlational study with a cross-sectional approach. The population is all third-trimester pregnant women at the Wilangan Nganjuk Health Center in October 2021 as many as 104 people, sampling was carried out for 2 weeks on October 2-16, 2021 by accidental sampling which obtained 56 people. Collecting data using a questionnaire sheet, then analyzed using Chi-Square statistical test with = 0.05. The results showed, that among 56 third trimester pregnant women, almost all of them had good knowledge, as many as 49 people (87.5%), most of them had a good attitude about the risk of exposure to Covid-19, namely 36 people (64.3%), most of them were ready. in preparing for childbirth during the Covid-19 Pandemic, as many as 34 people (70.7%). The results of the statistical test showed that there was a relationship between knowledge about the risk of exposure to Covid-19 and preparation for delivery of pregnant women in the third trimester with a p-value of = 0.012, and there was a relationship between attitudes and preparation for delivery of pregnant women in the third trimester with a p-value of = 0.024. Pregnant women can absorb information about Covid-19 to increase knowledge about the risk of exposure to Covid-19 so that it can be used as a prevention and control measure for Covid-19 so that pregnant women can go through pregnancy and childbirth in a healthy, safe, and no accompanying complication.